Circulation characteristics of bat coronaviruses linked to bat ecological factors in Korea, 2021–2022 - Min Chan Kim; Seong Sik Jang; Thi Van Lo; Ji Yeong Noh; Hyun A. Lim; Ha Yeon Kim; Da Young Mun; Kihyun Kim; Taek-Woo Lee; Yong Gun Choi; Sun-Woo Yoon; Dae Gwin Jeong; et al. (Virulence)
Considering that bat ecology alterations may be linked with pathogen spillover, research on bat coronaviruses, particularly on the infection and transmission pattern among bats in relation with their ecology, is essential. We captured bats distributed in Korea from 2021 to 2022, examined coronaviruses in oral swabs, feces, urine, and ectoparasites, and were able to detect alphacoronavirus. We investigated coronaviruses, but noted no substantial differences in the body condition index in the coronavirus-positive bats. Binary logistic regression analysis revealed that bat ecological factors that were significantly associated with coronavirus-positive were roost type, sample type, and bat species. Coronavirus-positive ectoparasite cases suggested additional study on the potential role of them as the viral transmission vectors or fomites. Reinfection of a different coronavirus in recaptured bats was evident, suggesting the possibility that coronavirus circulation can evade the potential protective immunity acquired from previous coronavirus infections. The present findings provide comprehensive information on the coronaviruses transmission dynamics within bat populations linked with bat ecology.